Dog and cat owners' use of online Facebook groups for pet health information. (29th May 2021) - Kogan, Lori R.; Little, Susan; Oxley, James
Abstract: Background: Facebook is a frequently used social media platform and is often used for human health information, yet little research has been conducted on how pet owners use Facebook pet groups to obtain and share pet health information. Method: This study was designed to assess how pet owners use dog and cat Facebook groups to provide and receive pet health advice and their perception of these groups' trustworthiness. Two comparable questionnaires (dog and cat owners) were developed and distributed through an online survey platform. Results: Results suggest that Facebook groups are a common source of pet health information, with 56.2% of dog owners and 51.8% of cat owners reporting receiving health information through Facebook groups. Similar numbers report giving health information through Facebook groups: 55.0% of dog owners and 57.9% of cat owners. Dog health information most commonly exchanged related to dermatology, gastroenterology and orthopaedics and the most common cat health information focused on gastroenterology, renal and urinary‐related issues. While the majority of Facebook users report feeling that Facebook groups are not a trustworthy source of pet health information, a substantial minority of users do appear to be influenced by these groups. Conclusion: Approximately 50% of cat and dog owning respondents either give or receive pet health advice through Facebook groups. These results suggest that many owners deem Facebook groups as useful, but not entirely trustworthy, sources of information.